Pastoralists picture land use - Rossi, Massimiliano; Rizzi, Italo (Technical Centre for Agricultural and Rural Cooperation, 2009)
A team of researchers combine maps, satellite images and participatory mapping techniques to develop an accurate picture of land use among pastoralists in southern Ethiopia